Analisis Faktor-Faktor Yang Mempengaruhi Jumlah Pembelian Produk Lapis Minang Nantigo - Lassefrianti; Alpon Satrianto (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
This study aims to determine the effect of income, prices of other goods, tastes, services and promotions on the number of purchases of Lapis Minang Nantigo products. This type of research is a quantitative study that uses primary data with a sample of 70 respondents from Lapis Minang Nantigo consumers. Data analysis used multiple linear regression analysis. The results showed that there was a positive and significant effect of income, taste and promotion on the number of purchases of Lapis Minang Nantigo products. Prices of other goods and services had no effect on the number of purchases of Lapis Minang Nantigo products. There is a significant effect of income, prices of other goods, services, tastes and promotions simultaneously on the number of purchases of Lapis Minang Nantigo products. It can be concluded that income, tastes and promotions can increase the number of consumer purchases of Lapis Minang Nantigo products.